DIGITAL ECONOMY AND ITS DEVELOPMENT FACTORS - Dilyora Xashimova Pakhritdinovna (Scholar Express Journals, 2024)
Currently, digital economy and their development factors are significantly influenced in many developed countries, and digital economy also plays an important role in the life of society. In this article, you can find answers to questions about the digital economy, such as "What is the digital economy?", "Tasks and goals of the digital economy", "Obstacles to the development of the digital economy in Uzbekistan".
Keywords: Digital economy; economics; market economy